The data & AI imperative designing strategies for exponential growth - Pierson, Lillian (John Wiley & Sons, Inc., 2025)
"This book covers data landscape analysis, use case identification, planning and strategy development, implementation oversight, and evaluation and scaling of data initiatives. It focuses on applying pre-trained generative AI models rather than developing custom LLMs, which are costly and complex. Using a tested framework, the book guides you in aligning data resources with business objectives, selecting impactful use cases, crafting effective strategies, and ensuring successful execution and scaling of AI initiatives"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Business -- Data processing; Artificial intelligence -- Economic aspects; Artificial intelligence -- Financial applications; Business planning; Gestion; Informatique; Intelligence artificielle; Aspect économique; Intelligence artificielle; Applications financières